Cephalometric Assessment of Condylar Position among Individuals with Different Skeletal Malocclusion Patterns - Poudel, P; Dahal, S (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: There are variations in growth and orientation of cranial base region where the maxilla and mandible articulate. This leads to differential movement of the maxilla and mandible causing changes in glenoid fossa and condylar position. Therefore, this study was conducted to determine the condylar position in patients with different skeletal sagittal malocclusion patterns.Methods: An analytical cross-sectional study was conducted among 165 individuals, having skeletal Class I, Class II and Class III relationship (55 in each group) selected by convenience sampling method after receiving ethical approval and informed consent. Lateral cephalograms were taken and measurements for determining condylar position were done and compared among three groups. Data were analyzed in SPSS version 16. Kruskal-Wallis H test was used to determine the mean difference in between condylar positions of three skeletal malocclusion patterns and Mann-Whitney U test was done for their pairwise comparison.Results: There was no significant difference in posterior cranial base length (P=0.200) and saddle angle (P=0.517) in three skeletal malocclusion class groups. However, the three malocclusion patterns showed significant differences in gonian angle (P=0.001) and articular angle (P=0.013). Significant moderate negative correlation in saddle angle and articular angle (P